Eksistensi Belian Sasak sebagai Pengobatan Alternatif Tradisional di Era Kemajuan Medis Modern di Kembang Sari Lombok Timur - Irdatul Haliza; Muhammad Shulhan Hadi; Suhupawati Suhupawati (Universitas Hamzanwadi, 2024)
This study aims to analyze the existence of Belian Sasak as a traditional alternative medicine amidst the advancement of modern medical treatment and its impact on the community in Dasan Ketangga, Kembang Sari, East Lombok. Using qualitative research methods with a phenomenological approach, this study involved in-depth interviews with four Belian Sasak, community leaders, and service users. The results show that Belian Sasak traditional medicine still exists and is trusted by the community despite increasingly sophisticated medical treatments. The main factors maintaining this existence are family factors and belief in ancestral heritage. The impacts of Belian Sasak's existence include: (1) helping the community in terms of treatment costs because there is no fixed tariff; (2) serving as an alternative treatment for diseases that cannot be cured medically, especially those caused by spiritual factors; and (3) preserving ancestral knowledge about traditional medicinal plants. This study concludes that Belian Sasak not only functions as a healer but also as an agent of local wisdom preservation that plays an important role in the Sasak community's health system.